Worm expulsion is independent of alterations in composition of the colonic bacteria that occur during experimental Hymenolepis diminuta-infection in mice. (3rd May 2020) - Shute, Adam; Wang, Arthur; Jayme, Timothy S.; Strous, Marc; McCoy, Kathy D.; Buret, Andre G.; McKay, Derek M.
ABSTRACT: The tapeworm Hymenolepis diminuta fails to establish in mice. Given the potential for helminth-bacteria interaction in the gut and the influence that commensal bacteria exert on host immunity, we tested if worm expulsion was related to alterations in the gut microbiota. Specific pathogen-free (SPF) mice, treated with broad-spectrum antibiotics, or germ-free wild-type mice were infected with H. diminuta, gut bacterial composition assessed by 16S rRNA gene sequencing, and worm counts, blood eosinophilia, goblet cells, splenic IL-4, -5 and -10, and colonic cytokines/chemokines mRNA were assessed. Effects of a PBS-soluble extract of adult H. diminuta on bacterial growth in vitro was tested. H. diminuta -infected mice displayed increased α and β diversity in colonic mucosa-associated and fecal bacterial communities, characterized by increased Lachnospiraceae and clostridium cluster XIVa. In vitro analysis revealed that the worm extract promoted the growth of anaerobic bacteria on M2GSC agar. H. diminuta- infection was accompanied by increased Th2 immune responses, and colon from infected mice had increased levels of IL-10, IL-25, Muc2, trefoil factor 3, and β2-defensin mRNA. SPF-mice treated with antibiotics, or germ-free mice, expelled H. diminuta with kinetics similar to control SPF mice. In both settings, measurements of Th2-immune responses were not significantly different across the groups. Thus, while infection with H. diminuta results in subtle but distinct changes to the colonic microbiota, we have no evidence to support an essential role for gut bacteria in the expulsion of the worm from the mouse host.